Evaluasi Kelayakan Usaha Teras Café di Kota Medan - Pelawi, Melati; Sitorus, Winda A; Sari, Yeni Indah; Harahap, Yulia (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to analyze the feasibility of a terrace cafe business in Medan City. One of the businesses that is growing rapidly in Medan City is the culinary business with a high level of competition. In order to compete, entrepreneurs need different types of culinary businesses. One type of business that is quite promising is Teras Cafe. Teras Cafe is one form of business in the culinary field that serves various types of food. In this study, a business feasibility analysis was carried out, on market aspects, technical aspects, legal and environmental aspects, human resource aspects, and financial aspects. The results show that the terrace cafe business has positive prospects. The data shows that this business is feasible to be developed in Medan City.